Perception on wild elephants among the public in Pahang, Malaysia - Othman, Mohd Shahwahid; Yong, Poh Lye; Sius @ Lawrencius, Teddy (Forestry Department Peninsular Malaysia, 2009)
A study was conducted via personal interviews from four districts; Kuantan, Rompin, Maran and Jerantut as well as Taman Negara in the state of Pahang to gauge the perceptions of the Malaysian public about the roles of wild elephants. A total of 220 respondents were interviewed. The approach adopted for valuing the conservation benefits of wild elephants was based on the Contingent Valuation Method (CVM). The CVM questionnaire contains a brief introduction of the study, a clear description of the hypothetical market concerning the wild elephants that are being valued, the payment vehicle for the willingness to pay (WTP) bid and the frequency of payment. The results showed that the mean maximum WTP for wild elephants perceived by the respondents was RM 5.86 per person with a median of RM 5.00 per person. Among the socio-economic variables, income and age were statistically significant in explaining the WTP bids. A positive WTP estimates suggested that wild elephants are important and society wants them to be protected, especially among the younger generations because of their greater exposure.